The Role of “Watershed Cases“ in Implementing Policies on Gender-Based Violence and Harassment in English Higher Education Institutions - Anna Bull (Open Gender Journal)
Tackling gender-based violence and harassment (GBVH) is an increasingly urgent task for higher education institutions (HEIs) globally. This article explores why HEIs take different approaches in the enactment of policies tackling GBVH. Through a comparative case study approach exploring two contrasting English HEIs, it focuses on one specific aspect of policy implementation that has been a particular challenge: formal report handling. One HEI had implemented national legal guidance in this area, while the other had not. In neither case were HEIs’ work in this area primarily driven by the national guidance; instead a proactive response in one HEI was shaped by a ‘watershed case’ of sexual violence. The article problematises analyses that homogenise the HE sector as taking a uniform approach on this issue, revealing a more complicated reality where institutional actors are highly aware of problems with institutional processes, and where cultures around GBVH shape policy implementation.